PARSING DOM Method Implementation for Web Scraping to Identify Pornographic Websites - Al Amin, Muhammad Insan (JESII: Journal of Elektronik Sistem InformasI, 2024)
When utilized improperly, internet technology can be a source of illegal information. One such instance is when pornographic content is published online. One of the numerous solutions that have been developed for DNS, or what is also referred to as DNS blocking, is that it is still subject to modification and re-access. The issue can be resolved by utilizing web scraping techniques to identify keywords based on text content, extract information from the website, and retrieve information using the DOM Parsing method. This allows text content to be gathered as a source of information related to the site's content, and the TF-IDF method can be used to calculate each website's weight known as the pornographic website. This study develops a reliable technique for locating pornographic content on the internet, which may be used with parental controls or content filtering systems.